Efficient Use of Mineral Raw Resources and Mining and Industrial Waste in the Regional Aspect - Syvyj, M J; Ivanov, Y A; Demyanchuk, P M; Panteleeva, N B; Havryshok, B B (Chemical and Materials Sciences: Developments and Innovations Vol. 6, 2024)
The present study Highlights about efficient use of mineral raw resources and mining and industrial waste in the regional aspect. Rational (effective) use of nature in the mineral and raw material base of the regions of Ukraine involves a number of measures that contribute to its optimization. At the same time, the solution to the specified problem includes the complex development of mineral deposits, complex use of mineral raw materials and mining waste, optimization of the structure of mining production and consumption of mineral raw materials. The modern interpretation of the rational use of subsoil resources extends to all stages of their development, including the issue of mining waste. At the moment, a huge amount of waste from the mining industry has accumulated on the territory of Ukraine, which creates not only economic and ecological but also significant social and demographic problems. The environmental situation has become particularly acute due to the accumulation of toxic waste, among which the most dangerous are heavy metals, petroleum products, and acid resins. The formation of sustainable development of Ukraine requires not only the development of newly discovered reserves of natural raw materials but also the use of man-made raw materials accumulated in more than 1,600 man-made deposits and objects. Optimizing the development of the country's mineral and raw material base requires an urgent solution at the state level to the problems that inhibit its growth and ecological improvement on the basis of rational use.